Privacy and security in e-commerce - Milan Mandić (Tržište, 2009)
Consumer distrust and concerns, mainly in regards to the protection of their private information and risk of being exposed to online frauds, have been the main obstacles in online commerce. This paper analyzes some of the most significant aspects of trust in e-commerce, with a focus on online security and privacy issues. With all the potential that e-commerce provides to both companies and consumers, it is in the interest of the company to increase trust among its online users. Some of the most common online crimes are analyzed and practical guidelines to achieving trust in the online environment are provided.